Comparison of the Acute Hematopoietic Capacities of Erythropoietin and U-74389G Concerning Hematocrit Levels - Tsompos, Constantinos; Panoulis, Constantinos; Toutouzas, Konstantinos; Triantafyllou, Aggeliki; Zografos, George; Papalois, Apostolos (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Aim: This study compared the hematopoietic capacities of erythropoietin (Epo) and antioxidant drug U-74389G, based on 2 preliminary studies. The provided results on hematocrit levels augmentation were co-evaluated in a hypoxia reoxygenation protocol of an animal model. Materials and Methods: Hematocrit levels were evaluated at the 60th reoxygenation min (for groups A, C and E) and at the 120th reoxygenation min (for groups B, D and F) in 60 rats. Groups A and B received no drugs, rats from groups C and D were administered with Epo; whereas rats from groups E and F were administered with U-74389G. Results: The first preliminary study of Epo non-significantly increased the hematocrit levels by 0.24%+1.38% (p-value=0.8586). The second preliminary study of U-74389G significantly raised the hematocrit levels by 3.16%+1.33% (p-value=0.0196). These 2 studies were co-evaluated since they came from the same experimental setting. The outcome of the co-evaluation was that U-74389G has approximately 12.66-fold higher hematopoietic potency than Epo (p-value=0.0000). Conclusion: The anti-oxidant capacities of U-74389G provide satisfactory acute hematopoietic properties; presenting approximately 12.66-fold hematocrit level rise than epo (p-value=0.0000).
Keywords: hematocrit levels